Recognition of two novel phenons of the genus Acinetobacter among non-glucose-acidifying isolates from human specimens - Nemec, A; Dijkshoorn, L; Jezek, P (Journal of clinical microbiology, 2000)
Genomic species diversity among 147 Acinetobacter clinical isolates not belonging to the A. calcoaceticus- A. baumannii (ACB) complex was investigated by phenotypic and genotypic identification methods. The isolates were obtained between 1991 and 1999 from numerous diagnostic laboratories in the Czech Republic and were studied by numerical probabilistic identification using two biochemical frequency matrices and amplified rDNA restriction analysis (ARDRA). Their final identification was derived from the combined phenotypic and ARDRA results. In total, 102 isolates were unambiguously (n = 89) or presumptively (n = 13) identified as A. lwoffii (n = 63), genomic species 13BJ/14TU (n = 9), A. johnsonii (n = 7), A. haemolyticus (n = 6), A. junii (n = 5), and other genomic species (n < 5 isolates each). Forty-five isolates could not be identified as belonging to any described species. Among the unidentified isolates two large groups of non-glucose-acidifying, nonhemolytic, and non-gelatinase-producing isolates were distinguished. These groups, designated phenon 1 (n = 17) and phenon 2 (n = 15), had distinctive phenotypic features and novel ARDRA profiles, which suggests that they represent hitherto undescribed Acinetobacter species. Phenon 2 included mainly clinically insignificant isolates from outpatients, while phenon 1 comprised clinically relevant isolates mostly from the blood of hospitalized patients, and its precise taxonomic definition may therefore be of medical importance. Overall, the development of practical methods for identification required for the elucidation of the biological significance of the (genomic) species within the genus Acinetobacter remains a challenging task.
Keywords: Acinetobacter; restrikční enzymy; lidé; glukosa; Glucose; Bacterial Typing Techniques; ribozomální DNA; infekce bakteriemi rodu Acinetobacter; fenotyp; DNA bakterií; Phenotype; Humans; Genotype; pravděpodobnost; techniky typizace bakterií; DNA, Bacterial; Česká republika; Probability; DNA, Ribosomal; Acinetobacter Infections; Czech Republic; DNA Restriction Enzymes; genotyp